2014
DOI: 10.1111/jtm.12142
|View full text |Cite
|
Sign up to set email alerts
|

Travelers With Sickle Cell Disease

Abstract: Background Sickle cell disease (SCD) is the most common genetic disease among persons with African ancestry. This article provides a background on SCD and reviews many important aspects of travel preparation in this population. Methods The medical literature was searched for studies about travel-associated preparedness and complications in individuals with SCD. Topics researched included malaria, bacterial infections, vaccinations, dehydration, altitude, air travel, and travel preparedness. Results There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In fact, during commercial flights in pressurised aircrafts, pressure of oxygen falls to the equivalent of breathing 15% oxygen (instead of 21%) at sea level [67]. As a consequence, patients with SCD and low baseline S pO 2 may develop severe in-flight hypoxaemia, potentially triggering vaso-occlusive pain crises and other SCD-related complications [68].…”
Section: Sdb and Hypoxaemiamentioning
confidence: 99%
“…In fact, during commercial flights in pressurised aircrafts, pressure of oxygen falls to the equivalent of breathing 15% oxygen (instead of 21%) at sea level [67]. As a consequence, patients with SCD and low baseline S pO 2 may develop severe in-flight hypoxaemia, potentially triggering vaso-occlusive pain crises and other SCD-related complications [68].…”
Section: Sdb and Hypoxaemiamentioning
confidence: 99%
“…The main advice is to prevent cooling down and ensure adequate fluid intake. The question whether these crises can be prevented with supplemental oxygen during flight has not yet been answered [ 30 , 31 ].…”
Section: Humidity and Hydrationmentioning
confidence: 99%
“…Diabetes has been identified as a risk factor for dengue, and so have other comorbidities such as hypertension, cardiovascular disease, and asthma [81,82]. Travelers with sickle cell disease are thought to be at increased risk of severe dengue [83]. Pregnant women are another group at high risk for severe disease, especially during the third trimester [84,85], and perinatal transmission to infants is recognized [86].…”
Section: Host Factors Relevant For Travelersmentioning
confidence: 99%
“…CYD-TDV is a live attenuated tetravalent vaccine with yellow fever 17D virus as backbone. In the age group of 9 years and above, efficacy against hospitalized dengue and severe dengue was high, 83 and 91% respectively [104]. Subsequently, in the year 2017, new long-term safety data were released which showed that the vaccine had a different performance depending on serostatus [105].…”
Section: Preventive Measures and Vaccinationmentioning
confidence: 99%